Q192R paraoxonase gene 1 (PON1) polymorphism and atorvastatin therapy effect in patients with type 2 diabetes mellitus (T2DM) - M. V. Kim; S. A. Skoryukova; A. A. Bystrova; E. I. Baranova; S. N. Pchelina (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Study objective: to estimate efficiency of atorvastatin therapy in patients with type 2 diabetes mellitus (T2DM), who are the carrier of various genotypes Q192R paraoxonase gene 1 (PON1). 386 T2DM patients, who have not received statin therapy before, and 187 healthy people were examined. All those examined were exposed to blood lipid profile testing and molecular genetic research. The atorvastatin treatment group included 164 T2DM patients with abnormality of lipids, their blood lipid profile values were assessed before and after 3 months of the therapy. Blood lipid profile values did not differ in type 2 diabetes mellitus patients (T2DM) - the carriers of different Q192R genotypes of paraoxonase gene 1 (PON1) polymorphism. Atorvastatin therapy decreased atherogenic lipoprotein levels in type 2 diabetes mellitus patients (T2DM) - the carriers of different Q192R genotypes of paraoxonase gene 1 (PON1) polymorphism, but reduction degree in the carriers of different Q192R genotypes differed - in Q192Q bearers it was greater than in the bearers of Q192R genotype of gene PON1 (р = 0,031). Atorvastatin 3-months therapy revealed greater reduction of total cholesterol in the carriers of Q192Q genotype of gene 1 (PON1) than in the carriers of Q192R genotype of gene 1 (PON1).